The Relationship between Triceps Skinfold Thickness and Age of Menarche Adolescent Girls in Surakarta City Junior High School - Kumala, Soebhita Hema; Widiretnani, Septin; Moelyo, Annang Giri (Smart Medical Journal, 2022)
Introduction: Triceps skinfold thickness is one of the anthropometric measurements that can indicate the nutritional status of overweight and obesity. Girls with obesity have 2.42 times the possibility of experiencing early menarche than girls with normal nutritional status. So it is estimated that the thicker triceps skinfold thickness, the earlier age at menarche in girls, but this opinion raises pros and cons through several studies, therefore the researcher wants to see the relationship between the two variables.Methods: This research is a cross-sectional observational analytic study with a purposive sampling method. All samples were asked to read the informed consent form and fill out a questionnaire regarding the age at menarche and measurements were made on the triceps skinfold thickness in the upper arm area using a skinfold caliper. Then the variables were analyzed univariate and bivariate using the Spearman test.Results: Based on the results of the Spearman correlation test between triceps skinfold thickness and age at menarche, it can be seen that the age at menarche has a significant relationship with triceps skinfold thickness as seen from p<0.05 (p=0.012). From the correlation test, it was found that there was a negative correlation between the sample's age at menarche and triceps skinfold thickness (r = - 0.188).Conclusion: There is a significant relationship between the age at menarche and triceps skinfold thickness in girls (age 11-16).